2014
DOI: 10.1186/1475-2891-13-8
|View full text |Cite
|
Sign up to set email alerts
|

The potential use of chickpeas in development of infant follow-on formula

Abstract: BackgroundUndernutrition during childhood is a common disorder in the developing countries, however most research has focussed much on its treatment rather than its prevention.ObjectiveWe investigated the potential of using chickpeas in infant follow-on formula production against the requirements of WHO/FAO on complementary foods and EU regulations on follow-on formula.MethodsChickpeas were germinated for 72 hours followed by boiling, drying and dehulling in order to minimise associated anti-nutrition factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 30 publications
(35 reference statements)
1
36
0
Order By: Relevance
“…The in vitro protein digestion has been studied and calculated using different methods to compare the digestibility of human milk, cow milk, as well as cow milk-, goat milk-, or soy protein-based IFs: proteolysis measurements using SDS-PAGE (Sodium dodecyl sulphate polyacrylamide gel electrophoresis) coupled with density methods [26][27][28], the pH drop method [27] or a more accurate method that uses a ratio of bioaccessible AA or nitrogen content in dialysate samples after digestion compared to the AA or nitrogen intake [29]. Moreover, the ability to use plant proteins in IFs has also been investigated, but most of the studies concerned the use of chickpea protein in follow-on formulas (6 to 12 months) [30,31]. Some others have focused on the capacity of pea protein [32] or different other legume proteins (chickpea, faba bean, lentil, and pea) [33] for probiotics encapsulation in follow-on IFs.…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro protein digestion has been studied and calculated using different methods to compare the digestibility of human milk, cow milk, as well as cow milk-, goat milk-, or soy protein-based IFs: proteolysis measurements using SDS-PAGE (Sodium dodecyl sulphate polyacrylamide gel electrophoresis) coupled with density methods [26][27][28], the pH drop method [27] or a more accurate method that uses a ratio of bioaccessible AA or nitrogen content in dialysate samples after digestion compared to the AA or nitrogen intake [29]. Moreover, the ability to use plant proteins in IFs has also been investigated, but most of the studies concerned the use of chickpea protein in follow-on formulas (6 to 12 months) [30,31]. Some others have focused on the capacity of pea protein [32] or different other legume proteins (chickpea, faba bean, lentil, and pea) [33] for probiotics encapsulation in follow-on IFs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the little amount of fat in Shadameen, this supplement is rich in protein and vitamin B1, B2, B6, Magnesium, Phosphorus and partly in zinc. Investigation of potential use of chickpeas in infant follow-on formula, found that the protein content was high and that they meet the amino acid requirements of the WHO/FAO protein reference for children at 0–24 month’s ( 32 ). Protein and zinc have a strong effect on linear growth.…”
Section: Discussionmentioning
confidence: 99%
“…One potential commonly consumed food with prebiotic effect is chickpea. Chickpea-based follow-on formulae have been explored as a potential prevention for undernutrition 21 .…”
Section: Introductionmentioning
confidence: 99%